A review of marine microalgae-based lipids production: biosynthesis, technological advancements, and practical applications - Yang, Limin; Duan, Bomingxin; Lu, Qian (Frontiers in Nutrition, 2025)
Marine microalgae have emerged as a sustainable and renewable feedstock for lipid production, offering significant potential to address environmental challenges and feed resource scarcity. This review provides a comprehensive analysis of marine microalgae-based lipid production, integrating insights from biosynthesis, technological advancements, and practical applications. First, we elucidate lipid accumulation process in marine microalgae, focusing on metabolic regulation, environmental stressors, and pharmaceutical functions. Next, this paper critically evaluate cutting-edge innovations in marine microalgae cultivation strategies, such as culture medium alternative, two-stage cultivation model, and microalgal cells immobilization. Last, the review highlights diverse applications of microalgal lipids in feed production for aquatic animals, livestock and poultry. Specific effects of dietary supplementation of microalgal lipid on the growth performance, health status and meat quality of animals are summarized. This review also assesses the technical challenges and practical viability of marine microalgae-based lipid production. Accordingly, some potential solutions which will promote the wide application of microalgal lipid in aquaculture and livestock/poultry farming are proposed. It is expected that this review can help researchers gain a more comprehensive understanding of marine microalgal lipids and encourage them to find out more actionable strategies to maximize the ecological and economic potential of marine microalgal lipids.